2000
DOI: 10.1128/cdli.7.4.540-548.2000
|View full text |Cite
|
Sign up to set email alerts
|

Need for an External Proficiency Testing Program for Cytokines, Chemokines, and Plasma Markers of Immune Activation

Abstract: The appearance of new diseases, therapies, or technologies often leads to new clinical laboratory measurements. This is often accompanied by novel instrumentation and reagents. Under these circumstances and until laboratory procedures and reagents are standardized and laboratory leaders and technologists have been trained, laboratories may differ substantially in analytic results with comparable samples, with resultant confusion and possible misinterpretation of clinical status. Thus, external performance eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…These considerations are not unique to multiplex assays, as prior studies focused on ELISAs demonstrated that the absolute concentration of cytokines measured by ELISA varied depending on which lab performed the testing, but trends in cytokine concentrations were consistent across multiple labs (5). Strategies to address assay reproducibility could focus on including an aliquot of a pedigreed control sample of human serum or plasma to be run on each assay or testing cytokines singly and randomly retesting 15 to 20% of samples, as has been suggested for radioimmunoassay and enzyme immunoassay testing (1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These considerations are not unique to multiplex assays, as prior studies focused on ELISAs demonstrated that the absolute concentration of cytokines measured by ELISA varied depending on which lab performed the testing, but trends in cytokine concentrations were consistent across multiple labs (5). Strategies to address assay reproducibility could focus on including an aliquot of a pedigreed control sample of human serum or plasma to be run on each assay or testing cytokines singly and randomly retesting 15 to 20% of samples, as has been suggested for radioimmunoassay and enzyme immunoassay testing (1).…”
Section: Discussionmentioning
confidence: 94%
“…These comparison studies have shown variable agreement among assays and have indicated that absolute cytokine concentrations differ across testing platforms. Such variability is not unique to multiplex assays, as proficiency testing has demonstrated that absolute concentrations of cytokines measured by a singleanalyte ELISA can vary widely from lab to lab, although a similar rank order of cytokine concentrations between samples is often preserved (5).…”
mentioning
confidence: 99%
“…The stimulation of cellular immunity associated with the activation of macrophages in the early phase causes an increase in the concentration of neopterin in urine, serum, and other body fluids. Thus, neopterin is considered an indicator of the activation of local macrophages in the early nonspecific phase of the human host defense immune system, although its role has not been fully clarified [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the absolute concentrations of cytokines and other markers of immune system activation measured in different laboratories can differ by two orders of magnitude [16]. It should be noted that these differences were detected when processing both the sera and supernatants; hence, they were determined by the quality of the used kits.…”
Section: Figure 3 Incidence Of Individuals With Rar Depending On Flimentioning
confidence: 99%